Socialization to Rebellion and Learning in the Light of Narrations of People Participating in Manifestations - Szczygieł, Przemysław (INSTED: Interdisciplinary Studies in Education & Society, 2018)
This text presents a fragment of empirical research carried out in the dissertation on learning mechanisms in the context of a rebellion (participation in protests and demonstrations). In the analyzed empirical material, the author identified the strands that show the problem called ?socialization to/of rebellion?. Examined people talked about the beginnings of their participation in demonstrations and protests, interalia in the context of family and peerial environment from an early age. The purpose of research, however, is not to reconstruct the process of socialization, but to understand and describe the mechanisms oflearning in the context of rebellious actions. The result of this learning is, among other things, a definedidentity.